Dual inoculation of Fusarium oxysporum endophytes in banana: effect on plant colonization, growth and control of the root burrowing nematode and the banana weevil - Paparu, P.; Dubois, T.; Coyne, Danny L.; Viljoen, Altus (2009)
The burrowing nematode (Radopholus similis (Cobb) Thorne) and the banana weevil (Cosmopolites sordidus Germar, Coleoptera: Curculionidae) are major pests of banana (Musa spp.) in the Lake Victoria basin region of Uganda. Among biological options to control the two pests is the use of non-pathogenic Fusarium oxysporum Schltdl.: Fries endophytes of banana. We investigated the ability of endophytic F. oxysporum isolates Emb2.4o and V5w2 to control the banana weevil and the burrowing nematode, alone and in combination. Plant colonization by the endophytes was determined by inoculating their chemical-resistant mutants separately and in combination, onto banana roots. Plant growth promotion was determined by measuring plant height, girth, number of live roots and fresh root weight at harvest, and control of the nematode and weevil was determined by challenging endophyte-inoculated plants with the pests 8 weeks after endophyte inoculation. Endophytic root colonization was highest in plants inoculated with both endophytes, compared with those inoculated with only one of the endophytes. Root colonization was better for isolate V5w2 than Emb2.4o. Dually inoculated plants showed a significant increase in height, girth, fresh root weight and number of functional roots following nematode challenge. Nematode numbers in roots were reduced 12 weeks after challenge of 8-week-old endophyte-inoculated plants. Significant reductions in weevil damage were observed in the rhizome periphery, inner and outer rhizomes, compared with endophyte non-inoculated controls. We conclude that dual inoculation of bananas with endophytic isolates Emb2.4o and V5w2 increases root colonization by the endophytes, reduces nematode numbers and weevil damage, and enhances plant growth in the presence of nematode infestation.